2012
DOI: 10.1121/1.3662048
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of thermal effects in antivascular ultrasound therapy

Abstract: Antivascular ultrasound consisting of low-intensity sonication in the presence of circulating microbubbles of an ultrasound contrast agent has been demonstrated to disrupt blood flow in solid cancers. In this study a mathematical framework is described for the microbubbleinduced heating that occurs during antivascular ultrasound. Biological tissues are modeled as a continuum of microbubble-filled vasculature, cells, and interstitial fluids with compressibility equal to the sum of the compressibility of each co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 29 publications
(50 reference statements)
0
31
0
Order By: Relevance
“…It has been demonstrated that thermal, mechanical, such as cavitation and other non-linear mechanisms, and sonochemical effects are likely to contribute to the anti-vascular activities of microbubbles (7). These acoustic mechanisms may act either to directly or indirectly damage vascular structure by inducing tissue response to the thermal, mechanical or sonochemical effects (7).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been demonstrated that thermal, mechanical, such as cavitation and other non-linear mechanisms, and sonochemical effects are likely to contribute to the anti-vascular activities of microbubbles (7). These acoustic mechanisms may act either to directly or indirectly damage vascular structure by inducing tissue response to the thermal, mechanical or sonochemical effects (7).…”
Section: Discussionmentioning
confidence: 99%
“…Heating is produced by the absorption of US energy through viscous damping of oscillating microbubbles (7). The network of tumor blood vessels is disorganized and tortuous and is likely to lead to the localized entrapment of microbubbles (7). As a result, the microbubbles are likely to reside in the US beam longer in the tumor tissue compared with the normal tissue.…”
Section: B Amentioning
confidence: 99%
See 3 more Smart Citations